Modulation of protease expression by the transcription factor Ptx1/PITX regulates protein quality control during aging. - Jiao, J.; Curley, M.; Graca, F.A.; Robles-Murguia, M.; Shirinifard, A.; Finkelstein, D.; Xu, B.; Fan, Y.; Demontis, F. (Cell reports, 2023)
Protein quality control is important for healthy aging and is dysregulated in age-related diseases. The autophagy-lysosome and ubiquitin-proteasome are key for proteostasis, but it remains largely unknown whether other proteolytic systems also contribute to maintain proteostasis during aging. Here, we find that expression of proteolytic enzymes (proteases/peptidases) distinct from the autophagy-lysosome and ubiquitin-proteasome systems declines during skeletal muscle aging in Drosophila. Age-dependent protease downregulation undermines proteostasis, as demonstrated by the increase in detergent-insoluble poly-ubiquitinated proteins and pathogenic huntingtin-polyQ levels in response to protease knockdown. Computational analyses identify the transcription factor Ptx1 (homologous to human PITX1/2/3) as a regulator of protease expression. Consistent with this model, Ptx1 protein levels increase with aging, and Ptx1 RNAi counteracts the age-associated downregulation of protease expression. Moreover, Ptx1 RNAi improves muscle protein quality control in a protease-dependent manner and extends lifespan. These findings indicate that proteases and their transcriptional modulator Ptx1 ensure proteostasis during aging.